Effect of contrast taining on serum protein electrophoresis, SOD gene expression, power and complex movement performance for fencers - Ali, O. A.; Soliman, A. (Proceedings of First Joint International Pre-Olympic Conference of Sports Science and Sports Engineering. Volume III: Statistics and Managment in Sports., 2008)
The present study examined the Effect of Contrast Training on Serum Protein Electrophoresis, SOD Gene Expression , Power and complex movement performances . Twenty fencers (mean +/- SD age, 19 +/- 2.8 years), divided into (2) group (experimental group -10 fencers) and (control group -10 fencers) , the experimental group performed the contrast training ( weight and plyomctric ) for (12) weeks . On each occassion, 3 sets of 5 repetitions with 3 minutes of rest were performed as fast as possible. 1 minute after each set, and at the fifth and 10th minutes of recovery. The tests was measured before and after the training program. The increased significantly for Serum Protein Electrophoresis (total protein , albumin) and super oxide Dismutase (SOD) Gene Expression values, Power and complex movement performances after the training program, These data show that contrast loading with the use of low and moderate loads can cause an increase in Serum Protein Electrophoresis (total protein , albumin) and super oxide Dismutase (SOD) Gene Expression values, Power and complex movement performances